Analisis Pengaruh Media Pembelajaran Film Dokumenter Terhadap Motivasi Belajar Siswa - Indra Arif Maulana Saufi; M A Rizka (UNDIKMA, 2021)
The purpose of this study was to analyze the effect of documentary film learning media on student learning motivation. This study used an experimental method with one group design with a total sampling of 19 students. Data collection techniques using questionnaires, documentation and observation. The data analysis technique of this research is using statistical analysis. The results of this study indicate x2hitung 6.477> x2tabel 3.841 with a significant level of 5% and dk (fh-1) = 2-1 = 1, it is obtained that Ho is rejected and Ha is accepted, so it can be concluded that there is an influence of documentary film learning media on learning motivation of class VIII students. SMP Negeri 2 Sakra Barat.